2012
DOI: 10.1016/j.jvs.2011.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy is associated with superior clinical outcomes after endovascular treatment of critical limb ischemia

Abstract: Patients who were receiving statin therapy when they underwent interventions to treat CLI had significantly improved overall survival, primary and secondary patency, and limb salvage rates. Our findings suggest that statins should be part of the periprocedural treatment regimen and support further investigation into the beneficial effects of statins in patients undergoing endovascular treatment of CLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 44 publications
4
63
1
Order By: Relevance
“…Although there are a number of studies showing improved survival in patients on statins after vascular surgical procedures [14][15][16][17][18]21 or in those with a diagnosis of PAD, 10 there are a few that included only patients with peripheral revascularization procedures. [11][12][13][14][15] Only three of these studies showed survival benefit. [13][14][15] Schanzer et al reported a survival benefit at 1 year (86% vs 81%) with statins in their cohort of patients with CLI who participated in the PREVENT III trial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are a number of studies showing improved survival in patients on statins after vascular surgical procedures [14][15][16][17][18]21 or in those with a diagnosis of PAD, 10 there are a few that included only patients with peripheral revascularization procedures. [11][12][13][14][15] Only three of these studies showed survival benefit. [13][14][15] Schanzer et al reported a survival benefit at 1 year (86% vs 81%) with statins in their cohort of patients with CLI who participated in the PREVENT III trial.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] Only three of these studies showed survival benefit. [13][14][15] Schanzer et al reported a survival benefit at 1 year (86% vs 81%) with statins in their cohort of patients with CLI who participated in the PREVENT III trial. 13 Aiello et al 14 reported improved survival at 24 months in patients who had endovascular interventions for CLI (77% vs 62%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, statin therapy is associated with reduced restenosis rates after endovascular intervention,53, 54 and reduced rates of symptom recurrence after revascularization for intermittent claudication 54. Aiello et al showed in a retrospective study in 646 CLI patients that statins can improve limb salvage rates after endovascular interventions for CLI (limb salvage 83% versus 62% at 24 months) 55. The temporal trend of increasing AFS and reducing amputation rates reported by Benoit et al in no‐option CLI patients may also partly reflect a relation between improved secondary prevention and limb‐related outcomes 32.…”
Section: Trends In Medical Therapy For Padmentioning
confidence: 99%